Biofilm formation is not an independent risk factor for mortality in patients with Acinetobacter baumannii bacteremia - Chiang, Tsung-Ta; Huang, Tzu-Wen; Sun, Jun-Ren; Kuo, Shu-Chen; Cheng, Aristine; Liu, Chang-Pan; Liu, Yuag-Meng; Yang, Ya-Sung; Chen, Te-Li; Lee, Yi-Tzu; Wang, Yung-Chih (Frontiers in Cellular and Infection Microbiology, 2022)
In the past decades, due to the high prevalence of the antibiotic-resistant isolates of Acinetobacter baumannii, it has emerged as one of the most troublesome pathogens threatening the global healthcare system. Furthermore, this pathogen has the ability to form biofilms, which is another effective mechanism by which it survives in the presence of antibiotics. However, the clinical impact of biofilm-forming A. baumannii isolates on patients with bacteremia is largely unknown. This retrospective study was conducted at five medical centers in Taiwan over a 9-year period. A total of 252 and 459 patients with bacteremia caused by biofilm- and non-biofilm-forming isolates of A. baumannii, respectively, were enrolled. The clinical demographics, antimicrobial susceptibility, biofilm-forming ability, and patient clinical outcomes were analyzed. The biofilm-forming ability of the isolates was assessed using a microtiter plate assay. Multivariate analysis revealed the higher APACHE II score, shock status, lack of appropriate antimicrobial therapy, and carbapenem resistance of the infected strain were independent risk factors of 28-day mortality in the patients with A. baumannii bacteremia. However, there was no significant difference between the 28-day survival and non-survival groups, in terms of the biofilm forming ability. Compared to the patients infected with non-biofilm-forming isolates, those infected with biofilm-forming isolates had a lower in-hospital mortality rate. Patients with either congestive heart failure, underlying hematological malignancy, or chemotherapy recipients were more likely to become infected with the biofilm-forming isolates. Multivariate analysis showed congestive heart failure was an independent risk factor of infection with biofilm-forming isolates, while those with arterial lines tended to be infected with non-biofilm-forming isolates. There were no significant differences in the sources of infection between the biofilm-forming and non-biofilm-forming isolate groups. Carbapenem susceptibility was also similar between these groups. In conclusion, the patients infected with the biofilm-forming isolates of the A. baumannii exhibited different clinical features than those infected with non-biofilm-forming isolates. The biofilm-forming ability of A. baumannii may also influence the antibiotic susceptibility of its isolates. However, it was not an independent risk factor for a 28-day mortality in the patients with bacteremia.